Marketing Plan RMCR Minerals Consulting - Surveyor Tambang Nikel berbasis Digital - Tantri Yanuar Rahmat Shah; Maria Agnes Vetter; Aditianata Aditianata (Neolectura, 2023)
Nickel is one of the natural resources that is currently of concern throughout the world. The number of nickel exports from Indonesia in 2019 reached USD 1.7 billion or with a percentage of 37.2% of total exports in the world. Even with this data, Indonesia is the world's Nickel King. Then in September 2020, the total Mining Business Permits (IUP) and People's Mining Permits (IPR) in Indonesia reached 5,354 IUPs. These data indicate that many IUP holders carry out mining production. With the increasing intensity of production, the need for testing of existing materials also increases. Therefore, RMCR Minerals Consulting will be formed as a surveyor agency to examine the content found in these materials. However, it takes a well-planned marketing to be able to attract cooperation with corporate partners. The purpose of this research is to formulate a marketing plan for RMCR Minerals Consulting. This study uses quantitative and qualitative methods by analyzing internal and external factors from RMCR Minerals Consulting using weighting and narrative methods. The result of this research is that RMCR Minerals Consulting is a company that provides mining surveyors for partner companies in the mining sector. In establishing cooperation, of course, a marketing plan is needed to establish relationships with partner companies. In preparing its marketing plan, RMCR Minerals Consulting has a framework starting from implementing the strategy; formulating goals, objectives, and marketing strategies; determine segmenting, targeting, and positioning; formulate a marketing plan; and manage sales marketing.